Dolphins in the Ionian-Adriatic Basin. Hellenistic Moldmade Ware from Orikos, Southern Illyria (Excavations 2012–2020) - De Mitri, Carlo (Journal of Hellenistic Pottery and Material Culture, 2021)
Orikos is located at the southern end part of the Bay of Vlorë, in a lagoon area. Protected by the Karaburun peninsula, the site overlooks the Straits of Otranto, the southern section of the Adriatic kolpos, where the Ionian and the Adriatic Seas meet. In the early years of this century (2007–2010), the Albano-Swiss Mission carried out several activities to understand the archaeological complexity of this site and to define its life phases. Since 2016, a systematic excavation campaign took place in different areas of the settlement and, together with the excavations, a study of the pottery and of different other finds was carried out.